FACTORS IN CAPITAL STRUCTURE AND ITS INFLUENCE ON TOTAL DEBT RATIO OF AUTOMOTIVE INDUTRY - FILIA NINDIANI; ERIKA JIMENA ARILYN (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this study is to get the empirical results about determinant factors in capital structure and its influence on total debt ratio. Liquidity, growth opportunities, firm size, profitability, and firm age is used as the independent variables. Data of 8 automotive companies listed on IDX were collected for the period of 19982016 (19 years). The data is collected from secondary data by analyzing the financial statement of sample companies. Panel data analysis has been used to find out the regression based on data collection. Findings of this research showed that liquidity, profitability, and firm age have an influence partially on total debt ratio. While growth opportunities and firm size have no influence partially on total debt ratio.